Membangun Karakter Siswa melalui Pembelajaran Sosial Emosional Berbasis Experiential Learning - Yendra, Dinda (Jurnal Pendidikan Tuntas, 2025)
This research is motivated by the challenges of education in the globalization era, which demand a balance between academic proficiency and social-emotional maturity. The primary focus of this study is to explore the implementation of Social Emotional Learning (SEL) based on Experiential Learning as an innovative strategy for building student character at the primary education level. The method employed is library research, analyzing relevant literature from the last five years. The findings indicate that the integration of five core SEL competencies—self-awareness, self-management, social awareness, relationship skills, and responsible decision-making—through real-world experiences (experiential learning) significantly enhances students' resilience, learning motivation, and adaptability. The study reveals that the main obstacles to SEL implementation include a lack of teacher understanding, limited professional training, and high administrative burdens. However, using an experience-based learning approach is proven to provide deep reflection space for students to apply character values in their daily lives. In conclusion, SEL based on Experiential Learning is a strategic solution to bridge the gap between cognitive and non-cognitive aspects in the current education system. The success of this implementation depends heavily on the teacher's role as a facilitator and strong policy support to create an educational ecosystem that humanizes students.